Population fluctuations of formicidae (Hymenoptera) and araneae (Arachnida) in two tillage systems in the region of guaíra-Sp. - Haddad, Gianni Queiroz [UNESP]; Cividanes, Francisco Jorge [UNESP]; Martins, Ivan Carlos Fernandes [UNESP]; Correa, Lilian Roberta Batista [UNESP] (De Gruyter, 2012)
The objective of this study was to elucidate population fluctuations of spider and ant species in forest fragments and adjacent soybean and corn crops under no-tillage and conventional tillage systems, and their correlations with meteorological factors. From Nov 2004 to Apr 2007 sampling of these arthropods at Guaíra, Sao Paulo state was done biweekly during the cropping season and monthly during the periods between crops. To obtain samples at each experimental site, pitfall traps were distributed in 2 transects of 200 m of which 100 m was in the crop, and 100 m was in the forest fragment. Temperature and rainfall were found to have major impacts on fluctuations in population densities of ants of the genus, Pheidole, in soybean and corn crops both grown with conventional tillage and no tillage systems.
Keywords: biodiversity; Population dynamics; predators; weather